(untitled) (Proceedings OPTIMAL, 2024)
Diarrhea is a condition characterized by changes in the form and consistency of stool, becoming softer or more liquid, along with an increased frequency of bowel movements. One plant that can be used as an antidiarrheal is avocado peel (Persea americana Mill). The avocado peel contains alkaloids, terpenoids, flavonoids, and tannins, which are antibacterial agents. This study aims to test the antibacterial activity against diarrhea-causing bacteria, specifically Salmonella typhi and Escherichia coli. The methods used include extraction by maceration, phytochemical screening for the identification of secondary metabolites, and antibacterial activity testing using the broth dilution method. The results showed that the avocado peel extract yielded 13.97%. Phytochemical screening indicated that all secondary metabolite compounds tested positive. In the antibacterial activity test, the avocado peel extract killed S. typhi bacteria at concentrations of 150,000 ppm and 100,000 ppm, while E. coli at concentrations of 50,000 ppm and 25,000 ppm. It can be concluded that the avocado peel extract can kill diarrhea-causing bacteria at concentrations of 150,000 ppm and 100,000 ppm for S. typhi and 50,000 ppm and 25,000 ppm for E. coli.